Extended Kalman filtering for simultaneous phase and amplitude noise mitigation in WDM systems - Pakala, Lalitha; Schmauß, Bernhard (International Conference on Transparent Optical Networks (ICTON), 2015)
The proposed carrier phase and amplitude noise estimation (CPANE) algorithm using extended Kalman filter (EKF) has been employed for joint mitigation of linear and non-linear phase noise and amplified spontaneous emission (ASE) noise in wavelength division multiplexing (WDM) systems. Numerical investigations on polarization multiplexed (PM) 16-quadrature amplitude modulation (16-QAM) 28 Gbaud/s WDM systems show that the proposed EKF technique outperforms the other considered carrier phase estimation (CPE) methods in mitigating inter and intra-channel non-linearities, laser phase noise and ASE noise.
lhft_intern.bib::Pakala2015b